A COMPARATIVE STUDY OF FIVE-LEVEL HYBRID MULTILEVEL INVERTERS BASED ON A 3-LEG INVERTER - Nguyen Ngoc Minh Doan; Nguyen Thanh Nhan; Trang The Hieu; Nguyen Tan Hung; Tong Quoc Truong; Le Ngoc Thanh (HUIT Journal of Science, 2025)
A hybrid multilevel inverter (HMI) integrates a three-leg voltage source inverters (VSIs) with full-bridge or half-bridge modules, offering advantages such as a reduced number of electronic power switches, DC sources, and DC capacitors compared to traditional multilevel inverters. Despite these advantages, HMIs exhibit distinct characteristics. This study investigates differences in DC power distribution and output voltage quality when operating with a five-level output voltage. Comparative results are obtained through simulation models in MATLAB/Simulink, using consistent parameters for both inverter topologies.